DOI: 10.31274/rtd-180813-11796
|View full text |Cite
|
Sign up to set email alerts
|

Soil slope stability investigation and analysis in Iowa

Abstract: In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…A positive correlation between and bulk density has been reported in the literature as higher bulk density in most cases indicates higher effective stress (e.g., Ayers, 1987;Bardet et al, 2011). The values recorded herein are in a general agreement with the values reported by Lohnes and Handy (1968), Lohnes et al (2001), Yang et al (2005), and…”
Section: Mechanical Strengthsupporting
confidence: 93%
See 1 more Smart Citation
“…A positive correlation between and bulk density has been reported in the literature as higher bulk density in most cases indicates higher effective stress (e.g., Ayers, 1987;Bardet et al, 2011). The values recorded herein are in a general agreement with the values reported by Lohnes and Handy (1968), Lohnes et al (2001), Yang et al (2005), and…”
Section: Mechanical Strengthsupporting
confidence: 93%
“…Veeraraghavan (2007) for sites exhibiting relatively similar properties. For example, Lohnes et al (2001) reported values ranging between 6.91 ± 4.19 kPa and 7.65 ± 5.59 kPa, respectively, for loess with high plasticity and glacial till deposits found in Iowa (Prior,1976;Lohnes et al, 2001;Yang et al, 2005;Oneal, 2009). Yang et al (2005) reported values in the range of 2.7 to 12 kPa for glacial till soils with a texture of silt clay loam extracted across six (6) counties in southern Iowa.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…Furthermore, soil properties such as cohesion, friction angle, particle size, density, and water contents are very important in any simulation and analysis involving soil [20,21]. Results from previous studies have shown that changing of soil friction angles and cohesion could affect the bearing capacity of soil [22,23]. The results from Khezri et al showed that cohesion is very important to be measured in underground structures because cohesion increases with depth and each layer of soil has different cohesion [24].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-share function of the soil-nailing has been mostly ignored. However, as shown in many on-field experiments, the impact of soil-nailing shear on the anti-slipping effect can be significant and should not be ignored from the design consideration [2].…”
Section: Introductionmentioning
confidence: 99%